Turning the Tide on Poverty: Documenting impacts through Ripple Effect Mapping. Issue 3 (26th May 2016) - Welborn, Rachel; Downey, Laura; Dyk, Patricia Hyjer; Monroe, Pamela A.; Tyler-Mackey, Crystal; Worthy, Sheri L.
Abstract: As practitioners expand their efforts to promote civic engagement and action through the use of dialog, one of the nagging concerns is how to effectively and successfully measure and document the outcomes associated with these local activities. The organic nature of citizen-led initiatives makes this a particularly challenging area in which to guage results. One promising method, Ripple Effect Mapping (REM), is an effective, easy-to-use, and cost-efficient method of evaluating participatory programs. Evaluators used REM to document the impact of Turning the Tide on Poverty in the southern US. Additionally, the method visually mapped the capacity-building work of communities participating in Tide. Representatives from each community that participated in REM were able to identify multiple accomplishments that resulted from Tide. These accomplishments were categorized using the Community Capitals Framework. REM was a useful evaluation method that documented how the Tide initiative affected the participating communities' capitals.